Az adózói magatartás különféle magyarázatai - Semjén András (Hungarian Academy of Sciences, Institute of Economics, 2016)
– The so called classic model of tax compliance behaviour interprets the problem as an individual decision under risk made by a single taxpayer. After a concise description of this model our literature survey investigates whether the empirical results found in the literature corroborate the expectations suggested by the theory regarding the impacts of the main explanatory factors on tax compliance. The results are somewhat contradictory and/or inconclusive regarding the impact of income size and the level of tax rates on tax compliance. The expected positive relationship between the frequency of tax audits and compliance, however, seems to hold. The deterring effect of high tax fines on compliance seems to be less strong than expected. Nevertheless, in the case of high audit probabilities the impact of high fine levels may become stronger. These findings suggest that more realistic alternative models are needed to explain the behaviour of taxpayers then the one offered by the classic economics-of-crime approach. Having reached this conclusion we somewhat elaborate on the most important new paradigms explaining taxpayers' behaviour, including the following ones: tax compliance behaviour as determined by the social dilemma between contributing individually to public good provision and free riding; the heterogeneity of taxpayers as the main factor determining taxpayer behaviour; the implicit psychological contract paradigm; and, finally, the slippery slope paradigm that can somehow synthesize the positive attributes of the above paradigms and integrate the economic and psychological explanations of tax compliance behaviour. At last we deal separately with agent based simulations, an increasingly popular methodological innovation in the field, that proves a valuable tool in analysing the impacts of these new paradigms describing taxpayer behaviour.
Keywords: H26; H71; O17; C63; C91; 330; tax compliance; tax evasion; slippery slope paradigm; tax administration; government; coercion; trust; agent based simulation